1992
DOI: 10.1128/jb.174.14.4746-4752.1992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipopolysaccharide biosynthesis genes rfaK, rfaL, rfaY, and rfaZ of Escherichia coli K-12 and Salmonella typhimurium

Abstract: Analysis of the sequence of a 4.3-kb region downstream of rfaJ revealed four genes. The first two of these, which encode proteins of 27,441 and 32,890 Da, were identified as rfaY and rfaZ by homology of the derived protein sequences of their products to the products of similar genes ofSalmonella typhimurium. The amino acid sequences of proteins RfaY and RfaZ showed, respectively, 70 and 72% identity. Genes 3 and 4 were identified as rfaK and rfaL on the basis of size and position, but the derived amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…Whether the defective core or the reduction in the amount of O-antigen of the rfaX mutant affected the polar localization of IcsA remains to be determined. Although the rfaX gene has homology to E. coli rfaY (Klena et al, 1992b), it is not possible to compare the effects of rfaY mutations in different organisms, because defined rfaY mutants in E. coli or S. typhimurium have not been reported and the role of rfaY in LPS core synthesis was speculative (Schnaitman and Klena, 1993). An uncharacterized mutant of S. flexneri generated in a previous study, S2687, showed a defective LPS core having normally attached O-antigen chains (Okada et al, 1991b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the defective core or the reduction in the amount of O-antigen of the rfaX mutant affected the polar localization of IcsA remains to be determined. Although the rfaX gene has homology to E. coli rfaY (Klena et al, 1992b), it is not possible to compare the effects of rfaY mutations in different organisms, because defined rfaY mutants in E. coli or S. typhimurium have not been reported and the role of rfaY in LPS core synthesis was speculative (Schnaitman and Klena, 1993). An uncharacterized mutant of S. flexneri generated in a previous study, S2687, showed a defective LPS core having normally attached O-antigen chains (Okada et al, 1991b).…”
Section: Discussionmentioning
confidence: 99%
“…In the E. coli and S. typhimurium rfa loci, rfaZ and rfaK are located downstream of rfaY (MacLachlan et al, 1991;Klena et al, 1992b). rfaK is thought to be a GlcNAc transferase gene that is required for LPS core synthesis, and mutations in this gene reduced the size of LPS cores and almost abolished O-antigen attachment (Mä kelä and Stocker, 1984;MacLachlan et al, 1991;Klena et al, 1992a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…waaF encodes ADP-heptose : LPS heptosyltransferase II (Gronow, et al, 2000). The product of the waaL gene, Oantigen ligase, connects the inner core to the O antigen of LPS (Klena et al, 1992). mEp213 phage adsorption in the above three mutants showed a decrease of 25-35 % at 5 min and a decrease of~15 % at 10-15 min when compared with the adsorption using the wild-type strain W3110 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are several components of the gene cluster that appear to be the result of gene substitutions. In addition to the genes expected for synthesis of the S. boydii type 13 O antigen men- (24). However, there has clearly been deletion in orf10, and this gene is no longer functional.…”
Section: Resultsmentioning
confidence: 99%